Information and Communication Technology for Intelligent Systems (ICTIS 2017) - Volume 2 - Satapathy, Suresh Chandra; Joshi, Amit.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This volume includes 73 papers presented at ICTIS 2017: Second International Conference on Information and Communication Technology for Intelligent Systems. The conference was held on 25th and 26th March 2017, in Ahmedabad, India and organized jointly by the Associated Chambers of Commerce and Industry of India (ASSOCHAM) Gujarat Chapter, the G R Foundation, the Association of Computer Machinery, Ahmedabad Chapter and supported by the Computer Society of India Division IV - Communication and Division V - Education and Research. The papers featured mainly focus on information and communications technology (ICT) and its applications in intelligent computing, cloud storage, data mining and software analysis. The fundamentals of various data analytics and algorithms discussed are useful to researchers in the fiel d.
Design of High-Speed LVDS Data Communication link using FPGA -- Face super resolution by Tangential and Exponential Kernel Weighted Regression Model -- Monitoring of Distributed Resources based on Client-Server (single-hop) Mobile Agents in Homogeneous Network of Interconnected Nodes -- Energy Balanced Clustering Protocol using Particle Swarm Optimization for Wireless Sensor Networks -- A Survey of Computer Vision based Corrosion Detection Approaches -- Word Sense Ambiguity In Question Sentence Translation: a Review -- Implementing a hybrid crypto-coding algorithm for an Image on FPGA -- Realization of FPGA based PID Controller for speed control of DC motor using Xilinx SysGen.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence